Software platform product management in corporate IT: framework enhancement and evaluation - Mori, Vitor Serra (2023)
Digital transformation has permeated various aspects of our lives, revolutionizing how we access music, reconnect with old friends, and engage in instant payments. Within this transformative landscape, the ability of technology companies to connect with customer needs by effectively managing products has emerged as a critical capability. A customer-centric approach has gained even more significance as successful business models shift towards "owning the consumer." Consequently, corporate IT organizations have adopted product management practices, with an estimated 70% penetration projected for 2024. Adopting product management in IT organizations typically involves managing software directly supporting business operations and internal software platforms. The latter serves as a foundation for building the former, and its adoption can enhance agility, efficiency, and value creation through reuse and specialization. However, managing software platforms as products presents challenges in identifying opportunities, evaluating them, and ensuring ongoing relevance. This research focuses on the gaps in product planning in managing software platforms as a product in corporate IT organizations. By employing Design Science Research (DSR), a method commonly used in information science in which the research paradigm focuses on developing and validating prescriptive knowledge, an interpretive-constructivist perspective study aims to advance theoretical understanding while providing practical contributions. The research evaluated one existing software product management framework through interviews with software platform managers, proposed modifications, and assessed the progress made with the changes. The theoretical contributions lie in enhancing the understanding of IT organizations' software product management through prescriptive knowledge. In contrast, practical contributions are materialized by a context-aware framework proposal that can offer valuable insights for professionals in the study context and its organizations. Additionally, the project's research approach contributes to the broader field of Design Science Research by bringing a unique perspective for taking multi-stage DSR research; this one focused solely on evaluation and improvement cycles and a research method to evaluate two artifacts simultaneously. The timing of these contributions makes it particularly relevant given the projected increase in product management practices adoption and software platforms as an IT strategic option to create a competitive advantage in its organizations. Additionally, this research details specific challenges and nuances of managing software platforms as products, including topics and study suggestions for future research endeavors.